7 SQUADRON IN WORLD WAR II (PART 1: 1942) - Robinson, R.; Nortier, D. (Scientia Militaria - South African Journal of Military Studies, 2012)
On 12 January 1942, a new squadron entered service with the SAAF, No 7 Squadron. Capt D. H. Loftus, DFC was placed in command and given the task of training the new fighter squadron for service in the Middle East. Temporary headquarters were established at MAF (Mobile Air Force) Roberts Heights, and as officers and details reported daily the squadron gradually increased its strength and settled down. The teething troubles and problems, common in the formation of any new squadron, were quickly remedied and did not prevent the rapid transfer of Squadron headquarters to ZAS (Swartkop Air Station). By 15 January 1942 No 7 Squadron was located under canvas at ZAS, a fully operational unit of the SAAF.